A PERFORMANCE ANALYSIS OF IOT-BASED AIRPORT ROBOT CARRIER - Evy Cristy Romaito Tambunan; M. Rizky Syahputra; Benny Satria (Jurnal Scientia, 2023)
The large number of porters at Indonesian airports has resulted in frequent cases of lost or switched luggage. As a result of this problem on September 1, 2017 the management of Soekarno Hatta airport provided a policy to eliminate porter services at the airport. From the existing problems, a trolley control system was designed using an Arduino-based smartphone -MQTT Hive MQ with the aim of changing the trolley system (manual) at the airport to a trolley system that can be controlled using a smartphone and is able to provide information on the location of the trolley (location tracking) in real time to the owner via the internet. The design of this control system uses an Arduino Pro Mini Microcontroller that is connected to GPS, Ultrasonic sensors, ESP 8266, and DC motors. This trolley system has an average deviation rate of trolley position coordinate readings of 0.13%, an average deviation of distance readings against obstacles of 6%, and a delay in the execution of commands by the trolley to the Smartphone of 1.16 seconds.